Better Understanding Disasters by Better Using History: Systematically Using the Historical Record as One Way to Advance Research into Disasters. Issue 1 (March 2016) - van Bavel, Bas; Curtis, Daniel
This paper argues that the understanding of causes and effects of hazards and shocks could be furthered by making more explicit and systematic use of the historical record, that is, by using 'the past' as a laboratory to test hypotheses in a careful way. History lends itself towards this end because of the opportunity it offers to identify distinct and divergent social structures existing very close to one another on a regional level and the possibility this creates of making comparisons between societal responses to shocks spatially and chronologically. Furthermore, the basic richness of the historical record itself enables us to make a long-term reconstruction of the social, economic and cultural impact of hazards and shocks simply not possible in contemporary disaster studies material.